Mental Binary Opposition of Wednesday and Enid in Wednesday Series S1 Episode 1 and 4 - Ambarwati, Nisrina Dewi; Tawami, Tatan (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2024)
This research aims to analyze the binary opposition present in the characters of Wednesday and Enid in the Wednesday Addams series season 1: episode 1 and 4. This research finds the binary opposition between these characters and uncovers their meanings, drawing upon Levi Strauss’s theory of binary oppositions. The descriptive qualitative method is employed, and scenes and English subtitles from the Wednesday Addams series season 1: episodes 1 and 4, available on Netflix, are used as the data source. The research identifies four opposing mental states: darkness and lightness, taciturnity and talkativeness, rigid and flexible, and indifference and care. Wednesday Addams exhibits unique mental states compared to other characters, particularly Enid, her best friend. Each of these four opposing mental states carries meaning beyond their mental states. Keywords: Binary Opposition, Mental State, Characters, Character’s Meaning